Do We Know What We Need? Preference for Feedback About Accurate Performances Does Not Benefit Sensorimotor Learning - Bastos, F.; Tani, G.; Drews, R.; Riek, S.; Marinovic, Welber (American Psychological Association, 2018)
Previous research on skill acquisition has shown that learners seem to prefer receiving knowledge of results (KR) about those trials in which they have performed more accurately. In the present study, we assessed whether this preference leads to an advantage in terms of skill acquisition, transfer, and retention of their capacity to extrapolate the motion of decelerating objects during periods of visual occlusion. Instead of questionnaires, we adopted a more direct approach to investigate learners' preferences for KR. Participants performed 90 trials of a motion extrapolation task (acquisition phase) in which, every three trials, they could decide between receiving KR about their best or worst performance. Retention and transfer tests were carried out 24 hr after the acquisition phase, without KR, to examine the effects of the self-selected KR on sensorimotor learning. Consistent with the current literature, a preference for receiving KR about the most accurate performance was observed. However, participants' preferences were not consistent throughout the experiment as less than 10% (N = 40) selected the same type of KR in all their choices. Importantly, although preferred by most participants, KR about accurate performances had detrimental effects on skill acquisition, suggesting that learners may not always choose the KR that will maximize their learning experiences and skill retention.